Death at no cost? Persons with no health insurance claims in the last year of life in Switzerland - Radoslaw Panczak; Viktor von Wyl; Oliver Reich; Xhyljeta Luta; Maud Maessen; Andreas E. Stuck; Claudia Berlin; Kurt Schmidlin; David C. Goodman; Matthias Egger; Kerri Clough-Gorr; Marcel Zwahlen (BMC, 2018)
Abstract Background Lack of health insurance claims (HIC) in the last year of life might indicate suboptimal end-of-life care, but reasons for no HIC are not fully understood because information on causes of death is often missing. We investigated association of no HIC with characteristics of individuals and their place of residence. Methods We analysed HIC of persons who died between 2008 and 2010, which were obtained from six providers of mandatory Swiss health insurance. We probabilistically linked these persons to death certificates to get cause of death information and analysed data using sex-stratified, multivariable logistic regression. Supplementary analyses looked at selected subgroups of persons according to the primary cause of death. Results The study population included 113,277 persons (46% males). Among these persons, 1199 (proportion 0.022, 95% CI: 0.021-0.024) males and 803 (0.013, 95% CI: 0.012-0.014) females had no HIC during the last year of life. We found sociodemographic and health differentials in the lack of HIC at the last year of life among these 2002 persons. The likelihood of having no HIC decreased steeply with older age. Those who died of cancer were more likely to have HIC (adjusted odds ratio for males 0.17, 95% CI: 0.13-0.22; females 0.19, 95% CI: 0.12-0.28) whereas those dying of mental and behavioural disorders (AOR males 1.83, 95% CI:1.42-2.37; females 1.65, 95% CI: 1.27-2.14), and males dying of suicide (AOR 2.15, 95% CI: 1.72-2.69) and accidents (AOR 2.41, 95% CI: 1.96-2.97) were more likely to have none. Single, widowed, and divorced persons also were more likely to have no HIC (AORs in range of 1.29-1.80). There was little or no association between the lack of HIC and characteristics of region of residence. Patterns of no HIC differed across main causes of death. Associations with age and civil status differed in particular for persons who died of cancer, suicide, accidents and assaults, and mental and behavioural disorders. Conclusions Particular groups might be more likely to not seek care or not report health insurance costs to insurers. Researchers should be aware of this aspect of health insurance data and account for persons who lack HIC.